OWNERSHIP STRUCTURE, DIVIDEND PAYMENT, AGENCY COST AND CORPORATE VALUE (SUATU PENGUJIAN MODEL STRUKTURAL) - Isti Fadah (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
The agency problem come because of separation between ownership and management on large corporate, there is a conflict between shareholder as an owner and manager as an agent. Manager focus on high growth of corporate (low dividend) but the owner prefer high dividend. The aims of the research are (1) to analysis the effect of free cash flow, risk and ownership structure to dividend payment ,(2) to analysis the effect of free cash flow, risk and ownership structure to agency cost. (3) to analysis the effect of dividend payment to corporate value, and (4) to analysis the effect of and agency cost to corporate value The technique sampling is purposive sampling. Secondary data is used in this research. It is from financial report like balance sheet, financial statement and cash flow report. It is gotten from Indonesian Stock Exchange. The research period is 2000 up to 2006. It uses pooled data ( joint of time series data and cross section data) so the analysis units are 271 (n=271). To Analysis data is used descriptive analysis and also statistical analysis that’s name structural equation model (SEM). It uses structural equation model (SEM) because the model has a ladder causality relationship and several variable like ownership structure, agency cost, risk , dividend payment and corporate value are latent variables. The results show that (1) risk has a positive significant effect to the agency cost, It means that agency cost can reduce the risk especially high risk investment that manger can do. (2) Dividend payment has a positive significant effect to the corporate value, It supports the-birds-in-the-hand theory and (3) risk has a positive significant effect to the corporate value. It means that investor always care about risk of corporate where they will invest.